Using of Microsatellites to Study the Genetic Polymorphisms of SRYm18 Region in Iraqi Sheep - Hawraa Al-Mohamadawi; Asaad Y. Ayied (مجلة ديالى للعلوم الزراعية, 2021)
The origin of animals is usually determined by their paternal genotypes of the genes on the Y chromosome. In addition to the genes and their polymorphisms in the genome of mitochondria that are inherited through dams. In view of the lack of studies focusing on the genes of the Y chromosome in the world and their absence in Iraq. The aim of the present study was to identify the multiple genetic polymorphisms of the SRYM18 gene in the Arabi and Awassi sheep raised in Iraq. The study was conducted in the Genetic Engineering Laboratories - College of Agriculture, University of Basra, as well as in the Basra Genome Laboratory. The amplification of the SRYM18 gene showed genetic polymorphisms and gave a gene segment of (103-880) bp. The number of alleles of the SRYm18 gene was 13 alleles in the Arabi and 16 alleles in the Awassi breeds. The equilibrium test showed that the two breeds were under equilibrium. The two breeds were identical with nine alleles, while the number of special alleles for the Arabi breed was two, while the Awassi breed was distinguished by five. The number of rare alleles reached 20, of which seven were of the Arabi breed, and 13 of them were of the Awassi breed. Mean expected heterozygosity was 0.6386 with nonsignificant Fis for Arabi breed (0.1541) but significant for Awassi breed (0.2213). Mean neutrality was close to lower bound (0.1721) and (0.1270) for Arabi and Awassi breeds respectively